An Overview of Hydration Status and Its Relation to Occupational Heat Stress among Workers - Ade Mutiara; Ray Wagiu Basrowi; Saptawati Bardosono (Indonesian Nutrition Association, 2019)
Working in high temperature environment is unavoidable condition for an outdoor worker, especially the outdoor workers in to tropical countries such as Indonesia. Heat stress leads to various heat-related illnesses, such as heat stroke, hyperthermia, heat exhaustion, heat cramps or heat rashes. A mild and moderate heat stress usually less serious and did not harm general health condition, however it could cause individual fatigue and unfocused, which will interfere the working performance and productivity. Heat stress will had caused physiologic response of the body, as it needs to reduce the increased temperature inside the body; known as heat strain condition.